Immunity in young adult survivors of childhood leukemia is similar to the elderly rather than age-matched controls: Role of cytomegalovirus - Azanan, M.S.; Abdullah, N.K.; Chua, L.L.; Lum, S.H.; Abdul Ghafar, S.S.; Kamarulzaman, A.; Kamaruzzaman, S.; Lewin, S.R.; Woo, Y.L.; Ariffin, H.; Rajasuriar, R. (John Wiley & Sons, 2016)
Many treatment complications that occur late in childhood cancer survivors resemble age-related comorbidities observed in the elderly. An immune phenotype characterized by increased immune activation, systemic inflammation, and accumulation of late-differentiated memory CD57+CD28− T cells has been associated with comorbidities in the elderly. Here, we explored if this phenotype was present in young adult leukemia survivors following an average of 19 years from chemotherapy and/or radiotherapy completion, and compared this with that in age-matched controls. We found that markers of systemic inflammation—IL-6 and human C-reactive protein and immune activation—CD38 and HLA-DR on T cells, soluble CD (sCD)163 from monocytes and macrophages—were increased in survivors compared to controls. T-cell responses specific to cytomegalovirus (CMV) were also increased in survivors compared to controls while CMV IgG levels in survivors were comparable to levels measured in the elderly (>50years) and correlated with IL-6, human C-reactive protein, sCD163, and CD57+CD28− memory T cells. Immune activation and inflammation markers correlated poorly with prior chemotherapy and radiotherapy exposure. These data suggest that CMV infection/reactivation is strongly correlated with the immunological phenotype seen in young childhood leukemia survivors and these changes may be associated with the early onset of age-related comorbidities in this group.